Strategy of the Religious Harmony Forum: Realizing a Peaceful and Harmonious Life - Mu’is, Abdul (Journal of Islamic Education, 2025)
This research aims to explore the Strategy of the Religious Harmony Forum to Realize a Peaceful and Harmonious Life, specifically focusing on the role of the Religious Harmony Forum in building harmony, supporting, and inhibiting factors in building religious harmony. This research uses a qualitative approach with a descriptive design and uses observation, interviews, and documentation as primary data collection methods through direct observation and interviews with key stakeholders. Data analysis includes three steps: data reduction, data presentation, and concluding. The Jember Religious Harmony Forum (FKUB) prioritizes a collaborative strategy to build a peaceful and harmonious life amid diversity. Through regular silaturrahmi between religious leaders, FKUB strengthens tolerance and opens space for dialogue that encourages mutual understanding and early conflict prevention. In addition, FKUB is active in interfaith humanitarian programs that strengthen solidarity and demonstrate that cooperation in social action can reduce differences. FKUB relies on mediation and deliberation as effective resolution mechanisms when friction arises, maintaining social stability without exacerbating differences. By utilizing local culture such as Pandalungan, which is closely related to the values of inclusiveness, FKUB can instil awareness of the importance of harmonious coexistence despite facing challenges such as identity politics and limited resources.